De que adoecem e morrem as mulheres em São Paulo - Batista, Luís Eduardo; Almeida, Margareth Aparecida Santini de [UNESP]; Morita, Ione [UNESP]; Volochko, Anna; Rea, Marina Ferreira (Universidade de São Paulo (USP), Faculdade de Saúde Pública, 2000)
O estudo traça um perfil da morbi-mortalidade feminina no Estado de São Paulo, com enfoque nos problemas reprodutivos. A mortalidade foi estudada nos períodos 1979-81; 1986-88 e 1993-5, a partir do Sistema de Informação em Mortalidade (SIM/DATASUS) e a morbidade de 1996 foi obtida do Sistema de Informações Hospitalares (SIH/DATASUS). O artigo discute as principais causas de internação e morte das mulheres e aponta os desafios para as políticas públicas voltadas a saúde da mulher.

This study aims at outlining a female morbidity and mortality profile in the State of São Paulo, focusing on the reproductive problems and contributing to a better formulation of public policies for the sector. Mortality data were collected from the Mortality Information System (SIM/DATASUS), in the periods 1979-81; 1986-88 and 1993-95, and morbidity data were gathered from the Hospital Information System (SIH/ DATASUS) in 1996. It was observed that the female mortality rate has a decreasing trend; stagnation or reversion of the trend in mortality is due to emergence of AIDS, with a major impact on the reproductive period. Cardiac and cerebrovascular diseases stand out as causes of death. As to morbidity, the main reasons for hospitalization are related to pregnancy, labor and puerperium. followed by respiratory and circulatory diseases. Hospitalization rates in the countryside are higher than in the Metropolitan Area.
The female morbidity and mortality in the State of São Paulo
Keywords: morbi-mortalidade feminina; problemas reprodutivos; AIDS; doenças cardíacas; doenças respiratórias; female morbidity and mortality; reproductive problems; AIDS; cardiac diseases; respiratory diseases